What if everybody said that? - Javernick, Ellen (New York : Two Lions, 2018)
What if everybody chose to be kind? If you tell someone that they can't play with you, there's no harm done, right? But what if everybody said that? What if everybody forgot to be kind--and made fun of other kids' artwork at school, or told a fib, or refused to share with a person in need? The world wouldn't be a very nice place to live. But what if everybody thought before they spoke, so the world would be a kinder place? With clear prose and lighthearted artwork, this companion book to the bestseller 'What If Everybody Did That?' explores the power of words and shows kids that the things we say matter.
Kirkus Review, May 2018
2.0
K-3
Keywords: Kindness -- Juvenile fiction; Human behavior -- Juvenile fiction; Kindness -- Fiction; Behavior -- Fiction; Picture books